Calculating opacity in hot, dense matter using second-order electron-photon and two-photon transitions to approximate line broadening - Baggott, RA; Rose, SJ; Mangles, SPD (American Physical Society, 2020)
Calculations of the opacity of hot, dense matter require models for plasma line broadening. However, the most general theories are too complex to calculate directly and some approximation is inevitably required. The most widely used approaches focus on the line center, where a Lorentzian shape is obtained. Here, we demonstrate that in the opposite limit, far from the line center, the opacity can be expressed in terms of second-order transitions, such as electron-photon and two-photon processes. We suggest that this insight could form the basis for a new approach to improve calculations of opacity in hot, dense matter. Preliminary calculations suggest that this approach could yield increased opacity away from absorption lines.